Evaluación de la calidad de vida mediante el cuestionario diabetes - 39 en pacientes hospitalizados con diabetes mellitus tipo 2 - De La Cruz Miñano, Juan Diego (2015)
To evaluate the quality of life in patients with Diabetes 2 through the questionnaire Diabetes - 39. Material and Methods: A descriptive study, whose design was observational, analytical, prospective and cross-sectional was done. The study population were patients diagnosed with Diabetes Mellitus type 2 in the Internal Medicine service of Hospital Belen of Trujillo. The populations sample was 56 patients to whom the questionnaire was applied Diabetes - 39, during the period of January-June 2015. The instrument assessed the quality of life of these patients according to dimensions: Energy and Mobility, Diabetes Control,Anxiety and Worry, Social Burden, Sexual Functioning. Results: In patients who formed the study sample, selected by inclusion criteria, they found that the dimensions affected the male populations was Energy - Mobility (73.33), Anxiety - Worry (75) and Sexual Functioning (77.77), while for women it was the Diabetes Control (73.61) and Social Burden (66.66). Conclusion: The quality of life of patients evaluated on a Internal Medicine, according to the Diabetes-39 questionnaire is 70.94; therefore, the more scores larger than this value shows impact on quality of life, according to the standard established for this instrument